Distribution cryptosporidiosis of cattle in farms of a mountain zone of Dagestan - S. Sh. Abdulmagomedov; V. F. Nikitin (Российский паразитологический журнал, 2016)
Cryptosporidiosis in the republic of Dagestan is widely spread. Digestive tract diseases followed by severe debilitating diarrhea, cachexy, growth retardation, de- velopment delay, reduction of body resistance to other diseases causing cattle mor- tality are often registered in offspring of cattle in life-stock farms. Calf mortality in certain farms reaches a level of 40 % and can exceed it. Spread and composition of the Cryptosporidium species in cattle were studied in 2010-2012 in 16 farms, 13 areas in a mountain zone of Dagestan. In each farm calves between 7 and 30 days, offspring - between 6 months and 2 years of age and adult stock-weak and debili- tated animals with expressed gastroenteritis are examined. It is found that cryptos- poridiosis in cattle of a mountain zone is being registered during a winter-spring season (February -April). Cryptosporidium oocysts are detected in excrements of calves in the age of 6-7 days. In farms of a mountain zone of Dagestan two species of Cryptosporidium - C. parvum и C.muris in cattle are found. Spread of cryptos- poridiosis is caused due to lack of veterinary and sanitary supervision as well as bad housing conditions of cattle.